A narrow host-range and lack of persistence in two non-target insect species of a bacterial symbiont exploited to deliver insecticidal RNAi in Western Flower Thrips - Whitten, Miranda M. A.; Xue, Qi; Taning, Clauvis Nji Tizi; James, Reuben; Smagghe, Guy; del Sol, Ricardo; Hitchings, Matthew; Dyson, Paul (Frontiers in Insect Science, 2023)
Insecticidal RNAi is a targeted pest insect population control measure. The specificity of insecticidal RNAi can theoretically be enhanced by using symbiotic bacteria with a narrow host range to deliver RNAi, an approach termed symbiont-mediated RNAi (SMR), a technology we have previously demonstrated in the globally-invasive pest species Western Flower Thrips (WFT). Here we determine a very limited distribution of the two predominant bacterial symbionts of WFT, BFo1 and BFo2, among genome-sequenced insects. Moreover, we have challenged two non-target insect species with both bacterial species, namely the pollinating European bumblebee, Bombus terrestris, and an insect predator of WFT, the pirate bug Orius laevigatus. Our data indicate that whereas BFo1 could establish itself in both these non-natural hosts, albeit with no significant effects on insect fitness, BFo2 was unable to persist in either species. In terms of biosafety, these data, together with its more specific growth requirements, vindicate the choice of BFo2 for delivery of RNAi and precision pest management of WFT.